Formerly Incarcerated Community Health Workers Engaging Individuals Returning From Incarceration Into Primary Care: Results From the Transition Clinic Network - Aminawung, Jenerius A.; Harvey, Tyler D.; Smart, Jerry; Calderon, Joseph; Steiner, Anna; Kroboth, Elizabeth; Wang, Emily A.; Shavit, Shira (Frontiers in Public Health, 2021)
Over half a million individuals return from US prisons and many more from jails every year with complex health and social needs. Community health workers (CHWs) perform diverse roles to improve health outcomes in disadvantaged communities, but no studies have assessed their role as integrated members of a primary care team serving individuals returning from incarceration. Using data from participants who received primary care through the Transitions Clinic Network, a model of care that integrates CHWs with a lived experienced of incarceration into primary care teams, we characterized how CHWs address participant health and social needs during interactions outside of clinic visits for six months after participants established primary care. Among the 751 participants, 79% had one or more CHW interactions outside of the clinic documented. Participants with more comorbid conditions, longer stay during their most recent incarceration, and released with a prescription had more interactions with CHWs compared to those with fewer comorbidities, shorter stay and no prescription at release. Median number of interactions was 4 (interquartile range, IQR 2- 8), 56% were in person and the most common issues addressed (34%) were social determinants of health; with the most common being housing (35%). TCN CHWs perform a variety of functions for participants outside of scheduled primary care visits. To improve health outcomes among disadvantaged populations, CHWs should be able to work across multiple systems, with supervision and support for CHW activities both in the primary care clinic and within the community.